(untitled) (Journal of Environmental Microbiology and Toxicology, 2023)
Surfactants are substances that can reduce its surface tension during dissolved in water or liquid and produce foam or solid. Bacterial-degrading SDS can be used for the bioremediation of this toxic substance in aquatic bodies or in soil. In this study, the isolation, identification and characterization of a local SDS-degrading bacterium is reported. Samples were isolated from a local location that had a history in surfactant contamination. Screening results shows that the best SDS-degrader was identified as Enterobacter cloacae sp. strain AaMa. The optimum conditions for the Enterobacter cloacae sp. strain AaMa to degrade the SDS were at pH 7.5, temperature 30 °C and the best nitrogen source to degrade the SDS was sodium nitrate. The Km (app) and Vmax (app) of SDS-degrading enzyme were 0.1035 mM and 0.4851 µmol SDS per minute per mg protein, respectively.